Early Response to Dehydration Six-Like Transporter Family: Early Origin in Streptophytes and Evolution in Land Plants - Slawinski, Lucie; Israel, Abir; Paillot, Caroline; Thibault, Florence; Cordaux, Richard; Atanassova, Rossitza; Dédaldéchamp, Fabienne; Laloi, Maryse (Frontiers in Plant Science, 2021)
Carbon management by plants involves the activity of many sugar transporters, which play roles in sugar subcellular partitioning and re-allocation at the scale of the whole organism. Among these transporters, the ESL (Early response to dehydration Six-Like) monosaccharide transporters are still poorly characterised although they represent one of the largest sugar transporter subfamilies. In this study we used an evolutionary genomic approach to infer the evolutionary history of this multigenic family. No ESL could be identified in the genomes of rhodophytes, chlorophytes and the brown algae Ectocarpus siliculosus while one ESL was identified in the genome of Klebsormidium nitens providing evidence for the early emergence of these transporters in Streptophytes. A phylogenetic analysis using 519 putative ESL proteins identified in the genomes of 47 Embryophyta species, representative of the plant kingdom, has revealed that ESL proteins sequences can be divided into three major groups. The first group originated in the common ancestor of all spermaphytes (zeta: 340 million years ago), the second group in the common ancestor of Angiosperms (epsilon: 170-235 million years ago) and the third group before the divergence of rosids and asterids (gamma/1R: 117 MYA). In some Eudicots (Vitales, Malpighiales, Myrtales, Sapindales, Brassicales, Malvales et Solanales), the ESL family presents remarkable expansions of gene copies in relation with tandem duplications. The analysis of non-synonymous and synonymous substitutions by the dN/dS ratio of the ESL copies of the genus Arabidopsis has revealed that ESL genes are evolving under purifying selection even though the progressive increase of dN/dS ratios through the three groups suggests sub-diversification phenomena. To further explore the possible acquisition of novel functions by ESL monosaccharide transporters, we identified their gene structure and promoter cis-acting elements for Arabidopsis thaliana ESL genes. The expression profiling of the Arabidopsis ESL, unraveled gene copies that are almost constitutively expressed while others displaying organ-preferential expression patterns. This study provides an evolving framework to better understanding the roles of ESL transporters in plant development and response to environmental constraints.